2009
DOI: 10.1088/1742-5468/2009/04/p04009
|View full text |Cite
|
Sign up to set email alerts
|

Random tree growth by vertex splitting

Abstract: We study a model of growing planar tree graphs where in each time step we separate the tree into two components by splitting a vertex and then connect the two pieces by inserting a new link between the daughter vertices. This model generalises the preferential attachment model and Ford's α-model for phylogenetic trees. We develop a mean field theory for the vertex degree distribution, prove that the mean field theory is exact in some special cases and check that it agrees with numerical simulations in general.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…The methods in [3] were non-rigorous in this case but the results were correct as we confirm here. By Theorem 1.2 the asymptotic vertex degree densities (a i ) ∞ i=1 satisfy…”
Section: Uniform Partitioning Weights Letsupporting
confidence: 60%
See 4 more Smart Citations
“…The methods in [3] were non-rigorous in this case but the results were correct as we confirm here. By Theorem 1.2 the asymptotic vertex degree densities (a i ) ∞ i=1 satisfy…”
Section: Uniform Partitioning Weights Letsupporting
confidence: 60%
“…is diagonalizable. (Appears in Theorem 2.5 in [3].) It was shown that under these assumptions the limits ρ k := lim t→∞ E(n t,k )/t exist for 1 ≤ k ≤ d max and are the unique positive solutions to…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations